English-Taught Bachelor’s Programs in Europe - Sandstrom, Ann-Malin (International Higher Education, 2018)
In less than a decade, Europe has witnessed a 50-fold increase in the number of English-taught bachelor’s programs (ETBs). ETBs refer to programs that are taught in English and result in a first-cycle postsecondary education diploma. This development has sparked debates about their value and purposefulness. Yet, research conducted by the European Association for International Education (EAIE) and Study Portals, English-taught bachelor’s programs—Internationalising European higher education (2017), has shown that the overall effect of ETBs on higher education institutions and the higher education sector in general has been positive.